2020
DOI: 10.1080/07481187.2020.1824204
|View full text |Cite
|
Sign up to set email alerts
|

Subjective vitality and loneliness explain how coronavirus anxiety increases rumination among college students

Abstract: We investigated the relationship between coronavirus anxiety and rumination with subjective vitality and loneliness as mediators. The online sample included 356 Turkish young people (M ¼ 22.06, SD ¼ 4.43 years). The analysis indicated that the coronavirus anxiety was directly associated with subjective vitality, loneliness, and rumination. Subjective vitality and loneliness also had direct effects on rumination. Furthermore, the indirect effect of coronavirus anxiety on rumination was mediated by subjective vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 49 publications
7
53
1
Order By: Relevance
“…The present findings are also in line with earlier research outcomes regarding the association between loneliness and mental health and well-being [31,32]. More specifically, cross-sectional results from the context of current pandemic showed that loneliness is positively associated with negative indicators of mental health and negatively associated with positive indicators of mental health [19,20,33,34]. Moreover, studies demonstrated that psychological strengths were found to be effective in reducing mental health problems and improving well-being [8,33].…”
Section: Discussionsupporting
confidence: 91%
“…The present findings are also in line with earlier research outcomes regarding the association between loneliness and mental health and well-being [31,32]. More specifically, cross-sectional results from the context of current pandemic showed that loneliness is positively associated with negative indicators of mental health and negatively associated with positive indicators of mental health [19,20,33,34]. Moreover, studies demonstrated that psychological strengths were found to be effective in reducing mental health problems and improving well-being [8,33].…”
Section: Discussionsupporting
confidence: 91%
“…A study that examined loneliness and health-related behaviors in 8,688 older adults that live alone, found the average UCLA loneliness score to be 4.2 ± 1.4 in the tested population compared to our 17.6 ± 15.8-20.4 ± 14.5 ranges over the four time points (Shankar et al, 2011). Another study that examined the relationship between coronavirus anxiety and loneliness among college students had a lower mean loneliness score (14.4 ± 4.65) compared to our population (Arslan et al, 2020). Individuals who suffer from loneliness are more likely to experience depression (Matthews et al, 2016), anxiety (Cacioppo et al, 2006;Arslan et al, 2020), and negative mood (Loucks, 1980).…”
Section: Discussioncontrasting
confidence: 61%
“…Another study that examined the relationship between coronavirus anxiety and loneliness among college students had a lower mean loneliness score (14.4 ± 4.65) compared to our population (Arslan et al, 2020). Individuals who suffer from loneliness are more likely to experience depression (Matthews et al, 2016), anxiety (Cacioppo et al, 2006;Arslan et al, 2020), and negative mood (Loucks, 1980). Depression scores were highest during time point two compared to the other three time points, and there were differences between time point one and four.…”
Section: Discussionmentioning
confidence: 49%
“…The contributing factors to this psychological distress are the uncertainties, unpredictability, seriousness of the disease, myths, and social isolation due to lockdown. Due to the myths and misinformation about COVID-19 spread through media, people are experiencing health anxiety in this particular context (Arslan et al, 2020). As mentioned above, it is evident from the literature that death anxiety is a significant contributor to psychological distress in this pandemic.…”
Section: Discussionmentioning
confidence: 99%